Management of severe malaria in children: proposed guidelines for the United Kingdom. - Maitland, K; Nadel, S; Pollard, A; Williams, T; Newton, C; Levin, M (2005)
Malaria is the most important imported mosquito borne infection in the United Kingdom As preventive measures are never 100% effective, malaria should be suspected in any patient with "flu-like symptoms" who has travelled to malarious areas within a year Most cases of severe malaria result from a failure to expedite prompt "same day" diagnosis and initiate appropriate treatment in patients with suspected malaria Oral quinine and chloroquine or pyrimethamine with sulfadoxine should never be prescribed to treat falciparum malaria in children In children, the development of one or more features of severe or complicated malaria constitutes a medical emergency The emergency assessment of a child with severe malaria should follow the structured approach advocated by the Advanced Paediatric Life Support guidelines If in doubt: admit, monitor closely, and seek specialist advice.